Analisis Pola Konsumsi Makanan Cepat Saji Dan Dampaknya Terhadap Status Gizi Mahasiswa Di Masa Kuliah Daring - Hasbibiani (Jurnal Ilmu Kesehatan Terpadu Indonesia, 2025)
Changes in student lifestyle during online learning have impacted eating habits, particularly an increased consumption of fast food, which may affect nutritional status. This study aimed to analyze fast food consumption patterns and their effects on the nutritional status of students. A quantitative approach with a descriptive correlational design was employed. The study sample consisted of 120 students selected purposively. Data were collected through online questionnaires on the frequency of fast food consumption and nutritional status measurement using body mass index (BMI) and 24-hour dietary recall. Data analysis was performed using descriptive statistics, Pearson correlation, and simple linear regression. The results showed that most students consumed fast food 2–4 times per week, mainly burgers, fried chicken, and pizza. The frequency of fast food consumption was positively and significantly correlated with student BMI (r = 0.42; p < 0.01) and accounted for 17.6% of BMI variation. These findings indicate that fast food consumption patterns significantly influence students' nutritional status. Nutritional education and access to healthy food are essential to promote healthier eating habits in the era of online learning.